Seizoen 1969-70 : Galerij Lambermont. - Galerij Lambermont, Brussel (Brussel : Galerij Lambermont, 1969)
Van De Voorde, Andre ; Diez, Anto ; Oosterlynck, Jan ; Van Vosselen, Omer ; Loverie, Pierre ; De Bondt, Erwin ; Vermandere, Willem ; etc.
Andre Van De Voorde, 25.10.69 - 6.11.69 / Anto Diez, 8.11.69 - 20.11.69 / Jan Oosterlynck, 22.11.69 - 4.12.69 / Omer Van Vosselen, 6.12.69 - 18.12.69 / Drie kunstenaars, 20.12.69 - 2.1.70 / Pierre Loverie, 3.170 - 15.1.70 / Erwin De Bondt, 17.1.70 - 29.1.70 / Willem Vermandere, 31.1.70 - 12.2.70 / etc.
boek